2011
DOI: 10.1172/jci45816
|View full text |Cite
|
Sign up to set email alerts
|

Human breast cancer cells enhance self tolerance by promoting evasion from NK cell antitumor immunity

Abstract: NK cells are a major component of the antitumor immune response and are involved in controlling tumor progression and metastases in animal models. Here, we show that dysfunction of these cells accompanies human breast tumor progression. We characterized human peripheral blood NK (p-NK) cells and malignant mammary tumor-infiltrating NK (Ti-NK) cells from patients with noninvasive and invasive breast cancers. NK cells isolated from the peripheral blood of healthy donors and normal breast tissue were used as cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
494
2
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 540 publications
(554 citation statements)
references
References 87 publications
28
494
2
5
Order By: Relevance
“…10,21 HLA-E expression has been observed in hepatocytes and appears to be increased in human HCC by Granulin-epithelin precursor, a hepatic oncofetal protein overexpressed in HCC. 22 By contrast, the enrichment of NKp46-and NKp30-positive NK-cells in HCCs with worse prognosis is in apparent contradiction with the activating function of these receptors, even though the above mentioned low expression of CD3z may reflect poor or absent receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,21 HLA-E expression has been observed in hepatocytes and appears to be increased in human HCC by Granulin-epithelin precursor, a hepatic oncofetal protein overexpressed in HCC. 22 By contrast, the enrichment of NKp46-and NKp30-positive NK-cells in HCCs with worse prognosis is in apparent contradiction with the activating function of these receptors, even though the above mentioned low expression of CD3z may reflect poor or absent receptor signaling.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of NKcell receptors in mediating antitumor immune response is further supported by the identification of several mechanisms of immune escape, mainly consisting in the downregulation of activating receptors and their ligands, or alternatively in the upregulation of inhibitory receptor-ligand pairs. [9][10][11][12] Additional mechanisms of immune evasion have also been described, such as escape from NKG2D-mediated immunosurveillance through shedding of NKG2D ligand MICA. 13 Few data are available about the role played by NK receptor expression and signaling in the determination of HCC outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The case of B lymphocytes is also unclear: they correlate with tumor growth and invasion in murine models [44][45][46][47] but scarce observations associate a B cells signature to good prognosis in several human cancers [48][49][50]. Intratumoral NK cells have been reported to down regulate their activating receptors and to be associated to larger breast [51] and lung [28] tumors, but without clear impact on patients survival. In other cancers, however, NK cell density rather correlates with good prognosis [14].…”
Section: The Immune Contexture Of the Tumor Microenvironment Has A Mamentioning
confidence: 99%
“…It has been shown that NK cells from cancer patients’ PBMCs have decreased expression of activation receptors and functional defects; 49,50 we thus investigated if entinostat treatment could increase the activation phenotype of these NK cells. PBMCs from seven heavily pretreated metastatic breast cancer patients were treated for 48 hours with a clinically relevant exposure of entinostat or DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fact that NK cells from heavily pretreated breast cancer patients had phenotypic changes after exposure to entinostat similar to healthy donor NK cells was a key novel finding of our study since it has been shown that cancer patients often have dysfunctional NK cells that are lacking an active phenotype. 49,50 …”
Section: Discussionmentioning
confidence: 99%